The COVID-19 pandemic and remote working did not improve WLAN security - Lindroos Saku; Hakkala Antti; Virtanen Seppo (Netherlands, 2022)
In this article, we present an analysis of the COVID-19 pandemic’s effects on Wireless Local Area Network (WLAN) security and abundance in Southwest Finland. We hypothesised that the drastic increase in telecommuting caused by the pandemic would encourage many to update obsolete WLAN devices, improving the state of WLAN security and increasing WLAN deployment in the survey region. To test our hypotheses, data from seven WLAN surveys carried out between February 2020 and October 2021 was analysed. Surprisingly, although the results show a 50.2% increase in WLAN deployment during the second and fourth waves of the pandemic, this had no significant effect on WLAN security in the survey region. The survey data shows little change in the number of unencrypted networks and networks configured with vulnerable encryption protocols. While most of the located networks were encrypted with the secure WPA2 protocol, the number of networks configured with the newest WPA3 has not notably increased.
The 13th International Conference on Ambient Systems, Networks and Technologies (ANT) / The 5th International Conference on Emerging Data and Industry 4.0 (EDI40)